Filogenetik Ikan Kuro (Eleutheronema sp.) di Perairan Pesisir Merauke, Papua Selatan - Saleky, Dandi; Situmorang, Ferdinand C.; Welliken K., Marius A.; Pangaribuan, Rosa D. (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This research aims to identify kuro fish (Eleutheronema sp.) Â collected from the coastal waters of Merauke. Cytochrome Oxidase Subunit I (COI) Gene was amplified by the Polymerase Chain Reaction (PCR) method, using primers FISH F1 (5â€™-TCA ACC AAC CAC AAA GAC ATT GGC AC-3â€™) and FISH R1. (5â€™-TAG ACT TCT GGG TGG CCA AAG AAT CA -3â€™), while DNA data analysis uses Mega 11 software. Results research shows that DNA sequence obtained were 675 base pairs long with the identification result being Eleutheronema tetradactylum with a similarity level of 99.54 and 99.85% for each sample. Based on phylogenetic analysis and genetic distance, the two DNA sequences analyzed form the same clade with identification results with a genetic distance of 0.001. Analysis of genetic diversity found 2 haplotypes from the two samples. Both the Sample Have a small genetic distance because THEY are collected from the same waters DNA barcoding and phylogenetics can be used to identify species for management and conservation of species.